PERBEDAAN SUBJECTIVE WELL-BEING PADA PEREMPUAN BALI YANG MENIKAH SESAMA WANGSA DAN BERBEDA WANGSA - Vratasti, I Gusti Ayu Maya; Wilani, Ni Made Ari (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
Subjective wellbeing is a thorough assessment of the individual's life that involves cognitive and affective aspects. The cognitive aspect is reflected in the assessment of life satisfaction and affective aspect is reflected from the positive and negative affects felt by the individual, the happiness of individual is when positives affect more dominant than the negatives affect. Marriage is one of the most powerful predictors of subjective wellbeing . In the collective culture, happiness can be caused by social acceptance of their marital status. Wangsa is a social stratification system in Balinese society that divides people into specific groups based on lineage. Wangsa system affects the process and marriage system in Bali which resulted in the emergence of same and different wangsa marriages. Same wangsa marriage will be easier to obtain the consent of the parents marriage more than different wangsa marriage, as well as their social consequences that must be faced by a woman who married different wangsa. In modern times the implementation of wangsa system have been improper, and some rules related to different wangsa married have been more flexible compared to the ancient times. This study aimed to see the condition of subjective wellbeing in Balinese women who married the same and different wangsa. This study used quantitative methods. The sampling technique in this study was three-stage cluster random sampling. Total sample of 60 people, consisting of 30 Balinese women who married the same wangsa and 30 Balinese women married the different wangsa. Measure tool used was subjective wellbeing scale. Data analysis method used was independent sample t-test. The study stated that there was no difference of subjective wellbeing in Balinese women who married the same and different wangsa. Keyword: subjective wellbeing , balinese women, same wangsa married, defferent wangsa married.